Influence of Deformation and Fluids on Ti Exchange in Natural Quartz. Issue 12 (7th December 2021) - Bestmann, Michel; Pennacchioni, Giorgio; Grasemann, Bernhard; Huet, Benjamin; Jones, Michael W. M.; Kewish, Cameron M.
Abstract: Using a combination of microstructural, spectroscopic, and geochemical analyses, we investigate how subgrain rotation recrystallization and fluid migration affect Ti concentration [Ti] in naturally deformed quartz veins from the Prijakt Nappe (Austroalpine Unit, Eastern Alps). These coarse‐grained quartz veins, that formed at amphibolite facies conditions, were overprinted by lower greenschist facies deformation to different degrees. During the overprint, subgrain rotation recrystallization was dominant during progressive deformation to ultramylonitic stages. The initial [Ti] (3.0–4.7 ppm) and cathodoluminescence (CL) signature of the vein crystals decrease during deformation mainly depending on the availability of fluids across the microstructure. The amount of strain played a subordinate role in resetting to lower [Ti] and corresponding darker CL shades. Using a microstructurally controlled analysis we find that the most complete re‐equilibration in recrystallized aggregates ([Ti] of 0.2–0.6 p.m.) occurred (a) in strain shadows around quartz porphyroclasts, acting as fluid sinks, and (b) in localized microshear zones that channelized fluid percolation. [Ti] resetting is mainly observed along wetted high angle boundaries (misorientation angle >10–15°), with partial [Ti] resetting observed along dry low angle boundaries (<10–15°). This study shows for the first time that pure subgrain rotation recrystallization in combination with dissolution‐precipitation under retrograde condition provide microstructural domains suitable for the application of titanium‐in‐quartz geothermobarometry at deformation temperatures down to 300–350°C. Plain Language Summary: For over 10 years, the TitaniQ geothermometer has been used to constrain deformation temperatures in quartz‐rich rocks. The calibration of the thermometer rests on the direct correlation of the titanium trace element concentration in quartz with respect to the ambient temperature. However, the processes and parameters which lead to re‐equilibration of the Ti‐in‐quartz system during deformation are not yet fully understood. Here we analysed deformed quartz veins from the Eastern Alps applying a combination of microstructural, spectroscopic, and geochemical analyses. In contrast to recent studies which highlight the importance of stain, we show that the availability of free grain boundaries, fluids, and their partitioning play the dominant role in Ti resetting toward lower concentrations in our studied case of retrograde deformation. We employ a robust analytical approach to investigate the interplay between grain‐scale deformation, fluid‐rock interactions, and geochemical exchange during increasing strain in the quartz mylonites. With this approach, the microstructures representing most re‐equilibrated sites for the application of the titanium‐in‐quartz geothermometer can be readily identified, even at lower greenschist facies deformation conditions and a recrystallization regime dominated by subgrain rotation. Key Points: Ti‐in‐quartz re‐equilibration is possible during subgrain rotation recrystallization even at lower greenschist facies conditions Ti resetting depends on the availability of aqueous fluids along interconnected grain boundaries, independently of the accumulated strain Partial Ti resetting also takes place along dry subgrain boundaries